The Development of on Job Training Assessment Constructs and Elements for Construction Technology Students in Malaysian Vocational College - Abdul Musid, Nurhafizah; Mohd Affandi, Haryanti; Hussain, Siti Hamidah; Mustaffa Kamal, Mohd Firdaus; Abas, & Nor Haslinda (Journal of Technical Education and Training, 2019)
On Job Training (OJT) (organisation) assessment rubric is widely considered instrumental in assessing Diploma in Construction Technology students with required competencies to function effectively in the work environment.  OJT remains predominantly process-focused with little attention to the criteria in OJT (organisation) assessment rubric. The aim of this study is to develop constructs and elements for OJT (organisation) assessment rubric. The research design for this study is a survey that was carried out qualitatively through document analysis to identify the constructs and elements in the OJT (organisation) assessment rubric.  From meta data analysis, 110 elements are identified to be the constructs and elements in OJT (organisation) assessment rubric.  After the expert validation process using questionnaire form as an instrument, only 75 elements are valid to be included in the OJT (organisation) assessment rubric while 35 elements discarded.  The majority of experts agreed that four elements are suitable to be constructs of soft skills, 5 items are suitable to be constructs of technical skills while remaining 66 elements divided into technical skills and soft skills.  Based on the 66 elements, 45 elements are technical skills and 21 elements in soft skills.  Therefore, it is suggested to conduct a pilot study for the reliability of constructs and elements of developed OJT (organisation) assessment rubric of Diploma in Construction Technology.